2016
DOI: 10.1371/journal.pone.0168457
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Arnt/Hif1β Is Dispensable in Myofiber Type Determination, Vascularization and Insulin Sensitivity

Abstract: Aryl Hydrocarbon Receptor Nuclear Translocator/ hypoxia-inducible factor 1 beta (ARNT/ HIF1β), a member of bHLH-PAS family of transcriptional factors, plays a critical role in metabolic homeostasis, insulin resistance and glucose intolerance. The contributions of ARNT in pancreas, liver and adipose tissue to energy balance through gene regulation have been described. Surprisingly, the impact of ARNT signaling in the skeletal muscles, one of the major organs involved in glucose disposal, has not been investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Following activation, there were no differences noted in mouse weight or hind limb muscle mass between the ARNT mKO mice and littermate controls (Supporting Figure S2). The ARNT mKO mice exhibited 90% reduction in the skeletal muscle ARNT expression (Supporting Figure S2), similar to previous reports 13 . ARNT deletion in young mice hindered skeletal muscle regeneration in comparison to similarly treated littermate controls, as indicated by smaller regenerating muscle fibers on DPI 5 ( P < .001) and DPI 10 ( P < .001) in ARNT mKO mice (Figure 5A‐C).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Following activation, there were no differences noted in mouse weight or hind limb muscle mass between the ARNT mKO mice and littermate controls (Supporting Figure S2). The ARNT mKO mice exhibited 90% reduction in the skeletal muscle ARNT expression (Supporting Figure S2), similar to previous reports 13 . ARNT deletion in young mice hindered skeletal muscle regeneration in comparison to similarly treated littermate controls, as indicated by smaller regenerating muscle fibers on DPI 5 ( P < .001) and DPI 10 ( P < .001) in ARNT mKO mice (Figure 5A‐C).…”
Section: Resultssupporting
confidence: 89%
“…These findings suggest that the impaired muscle regeneration seen in the ARNT mKO mice was not likely dependent on vascular or perfusion changes within the muscle. Others have similarly demonstrated that constitutive skeletal muscle‐specific knockout of ARNT inhibits hypoxia signaling without limiting vasculogenesis 13 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the ability of circadian proteins and HIF1α to form functional heterodimers in a physiological context has been controversial ( Cowden and Simon, 2002 ). Although HIF1α/BMAL1 heterodimers are unable to support normal vascularization in HIF1β-deficient mouse embryos ( Cowden and Simon, 2002 ), it was recently demonstrated that muscle-specific deletion of HIF1β has no impact whatsoever on muscle vascularization ( Badin et al., 2016 ). This finding suggests that an alternate partner, perhaps BMAL1, may cooperate with HIF1α to support muscle vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%